Perancangan Aplikasi Helpdesk Menggunakan Pendekatan Knowledge Management System pada Jurusan Sistem Informasi UIN Syarif Hidayatullah Jakarta - Muthia Anggraini; Evy Nurmiati (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Syarif Hidayatullah State Islamic University of Jakartais an educational institution that is tasked with providing quality knowledge and education to students in educating the nation's children. In the current era of globalization, there is knowledge that must be managed for agencies. To achieve this, it is necessary to use existing information technology, namely the online-based Knowledge Management System application. In the world of education, a helpdesk application that helps in improving existing performance and competence. The helpdesk application is widely used by companies and agencies, this application helps facilitate the work of the university technician section. In addition, this helpdesk application makes it easy for students to report damaged campus facilities, so that the technician will make repairs quickly. By looking at this situation, we need a web-based helpdesk application that can coordinate information between technicians and students using the PHP programming languages and My SQL as database design.